PWE-069 Care of patients with end stage liver disease and refractory ascites remains suboptimal: need for earlier input from palliative care. (17th June 2017) - Macken, L; Hashim, A; Potts, J; Verma, S
Abstract : Introduction: Refractory ascites (RA) in end stage liver disease (ESLD) confers a poor prognosis in non-liver transplant (LT) candidates; therefore heralds a palliative stage of management. Standard care in RA is recurrent large volume paracentesis (LVP). Pathways in malignant ascites are well developed; medical ambulatory care units (ACU), long-term abdominal drains (LTAD) and palliative care input. Our aim was to assess the natural history of ascites in ESLD; particularly hospitalisation, LT referral, input from palliative care and eventual outcome. Method: This was a retrospective cohort study (January 2013-December 2015). RA was defined as per EASL Practice Guidelines. Electronic hospital records from a large teaching hospital in Southeast England were reviewed and relevant data collected.ć Results: A total of 419 cases met search criteria; 317 were suitable for inclusion. Aetiologies of ascites were malignant (53%) and chronic liver disease (CLD) (41%). Alcohol related liver disease (ARLD) was the commonest cause of CLD requiring LVP, n=82 (63%), followed by a combination of ARLD and non-alcoholic steatohepatitis (NASH), n=16 (12%). In the CLD group 63 (48%) underwent inpatient LVP, 12 (9%) on ACU, the remainder in both areas. Of those with CLD, 49 (37%) developed RA; 18 referred for LT assessment, of whom 6 (12%) were listed or underwent LT. The commonest barrier to LT referral was alcohol recidivism, 14 (29%). Median age at development of RA was 58 years (35-86), Model for End-Stage Liver Disease (MELD) 15 (8-29). Median number of LVPs in those with RA was 13 (4-62), time to development of RA from first episode of decompensation 808 days (34–2179) and from first LVP 102 days (0–1161). There were no statistically significant differences in baseline patient demographics, liver prognostic scores or renal function between those that did and did not develop RA. At last follow up, 22 (45%) individuals with RA were alive; median survival from RA diagnosis 179 days (45–771 days). In the RA cohort, 22 (45%) had documentation suggesting their care was palliative, however only 16 (33%) were referred for palliative care input and 13 (27%) had any advanced care planning. Conclusion: Approximately 40% of patients with ESLD and ascites requiring LVP developed RA. Baseline characteristics are unhelpful in predicting RA development. Since <20% are LT candidates, such individuals utilise significant hospital resources due to recurrent LVP. Our work supports calls to improve end of life care in ESLD and RA with earlier involvement of palliative medicine and novel strategies such as LTAD to transfer care into the community. Disclosure of Interest: L. Macken Conflict with: NIHR rfpb, A. Hashim: None Declared, J. Potts: None Declared, S. Verma Conflict with: NIHR rfpb